What's new at the zoo? : an animal adding adventure - Slade, Suzanne (Sylvan Dell Publishing, 2009)
Travel through the zoo and learn about zoo animals through rhyme. Count up all of the animals you have seen. Includes section "For Creative Minds" with cards and activities.